Opensim full-body model for athletes with a running-specific below the knee prosthesis - Krämer, L.; Zedler, M.; Heinrich, K.; Potthast, W.; Funken, J. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
To date, there is no comprehensive open-source tool to provide movement analysis of athletes using a running-specific prosthesis (RSP) with a below the knee amputation (BKA) to enable the calculation of corresponding inverse kinematics and dynamics. A combination of physical measurements, 2D imagery, 3D motion capture data and geometrical calculations were used to create a musculoskeletal full-body OpenSim model with subject-specific BKA structures. The model was able to reproduce athlete`s joint angles and joint moments of the lower extremities while allowing for movement comparison to non-amputee athletes. The model provides a motion analysis tool for athletes with a RSP in an open-source environment, providing qualitatively similar results to previous research, and lays the foundation for more insights into BKA athletes` muscle activity and acting muscle forces.